Jordan Generalized Centralizerhomo on Prime Rings. - Karim, Mazen (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
In this article we introduce the concepts of generalized centralizerhomo and Jordan generalized centralizerhomo on prime ring. The aim object of this paper we prove: Every Jordan generalized centralizerhomo of 2-torsion free prime ring is Jordan generalized triple centralizerhomo on .